One-Pot, Solvent-Free Allylation or Propargylation of Carbonyl Compounds Mediated by the in situ Generated Zn-Ag Couple - Yu, Changquan; Yang, Jian; Xia, Lingjie; Lu, Xiuyang (Asian Journal of Chemistry, 2012)
Zn-Ag couple which was in situ generated by zinc being oxidized with catalytic silver acetate was successfully applied to the one-pot and solvent-free allylation or propargylation of carbonyl compounds, in which high yields, regioselective addition, waste minimization and simple operation can be achieved.